Maternal and neonatal outcome and children’s development after medically assisted reproduction with in-vitro matured oocytes: a systematic review and meta-analysis - Strowitzki, Thomas; Bruckner, Thomas; Rösner, Sabine (Human reproduction update, 2021)
The aim of this systematic review was to evaluate the current evidence from IVM children of an impact of in-vitro culture of immature oocytes. Primary outcome parameters were birthweight and children’s development up to the age of 2 years. We also compared pregnancy pathologies and the outcome of IVM children and COS children in relation to maternal indications, in particular PCOS, and to the type of IVM protocols with or without ovulation trigger as the secondary outcome parameters.